2022
DOI: 10.1038/s41586-022-04902-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the resilience of plant immunity to a warming climate

Abstract: Extreme weather conditions associated with climate change affect many aspects of plant and animal life, including the response to infectious diseases. Production of salicylic acid (SA), a central plant defence hormone1–3, is particularly vulnerable to suppression by short periods of hot weather above the normal plant growth temperature range via an unknown mechanism4–7. Here we show that suppression of SA production in Arabidopsis thaliana at 28 °C is independent of PHYTOCHROME B8,9 (phyB) and EARLY FLOWERING … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
127
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 52 publications
4
127
1
Order By: Relevance
“…CPB60g encodes a master immune transcription factor that works in parallel with SARD1 to synthesize the plant defense hormone SA (Kim et al, 2022; Sun et al, 2015). In the absence of pathogen infection, CBP60g is expressed surrounding trichomes and in skirt cells at the base of trichomes (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…CPB60g encodes a master immune transcription factor that works in parallel with SARD1 to synthesize the plant defense hormone SA (Kim et al, 2022; Sun et al, 2015). In the absence of pathogen infection, CBP60g is expressed surrounding trichomes and in skirt cells at the base of trichomes (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that the OsCBL8–OsCIPK17 module can regulate growth and development and defense strategies by regulating IAA, ABA, and JA levels. A recent study has shown that SA is involved in plant hyperthermia and immune responses [ 28 ]. However, whether the regulation function of this module depends on SA requires further study.…”
Section: Resultsmentioning
confidence: 99%
“…Benzothiadiazole (BTH) is an analog of SA and, like SA, triggers systemic acquired resistance in plants and confers protection against Pst (Görlach et al, 1996; Kim et al, 2022). Since SA biosynthesis and signaling are essential for preventing water-soaking under LL (Fig.…”
Section: Resultsmentioning
confidence: 99%